Utilidad diagnóstica de la escala de demencia VIH (HDS) y la escala internacional de demencia VIH (IHDS) en la detección de trastorno neurocognitivo asociado al VIH en adultos - Elorreaga Julca, Rosa Erika (2021)
HIV infection has implications for all systems. Among the neurological alterations we have the HIV-associated neurocognitive disorder (HAND). Around 70% of this pathology is not recognized by the patient or the doctor on duty, therefore it is necessary to determine the diagnostic utility of the HIV dementia scale (HDS) and the international HIV dementia scale (IHDS) in the detection of HAND in adults, to identify this disorder early and establish prevention measures in order to reduce the evolution of this neurodegenerative disease. A monographic review was carried out with a bibliographic search in PubMed, SciELO, Redalyc, Science Direct, Scopus, Web of Science, Latindex; journals such as The New England Journal of Medicine, Nature Reviews, and The Lancet; and in Google Scholar; and 14 articles were selected that met our inclusion and exclusion criteria. The results of this review show that the IHDS (S: 36-100%) is more sensitive than the HDS (S: 41-97%), both scales require little time to administer (3-10 minutes), minimal costs and they can be administered by non-specialized personnel. Finally, we observed that both the HDS and the IHDS are useful in the detection of HAND in adults.